2016
DOI: 10.1371/journal.pone.0153877
|View full text |Cite
|
Sign up to set email alerts
|

The Evidence for Intravenous Theophylline Levels between 10-20mg/L in Children Suffering an Acute Exacerbation of Asthma: A Systematic Review

Abstract: BackgroundIntravenous theophyllines are a second line treatment for children suffering an acute exacerbation of asthma. Various guidelines and formularies recommend aiming for serum theophylline levels between 10-20mg/l. This review aims to assess the evidence underpinning this recommendation.MethodsA systematic review comparing outcomes of children who achieved serum theophylline concentrations between 10-20mg/l with those who did not. Primary outcomes were time until resolution of symptoms, mortality and nee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…The remaining reviews extracted the mean ± standard deviation of drug level achieved across participants [8, 10, 16]. One review extracted the timing of drug measurement [11], and two reviews performed separate analyses depending on the type of assay used [13, 17].…”
Section: Resultsmentioning
confidence: 99%
“…The remaining reviews extracted the mean ± standard deviation of drug level achieved across participants [8, 10, 16]. One review extracted the timing of drug measurement [11], and two reviews performed separate analyses depending on the type of assay used [13, 17].…”
Section: Resultsmentioning
confidence: 99%
“…Few studies primarily investigate the optimum dosing strategies in children [ 18 ] Therefore, we used a systematic review technique which anticipates various study designs, similar to the methodology we recently used to examine the evidence around therapeutic ranges for aminophylline [ 17 , 19 ]. We decided a priori that the most relevant study type would be a comparison of randomised controlled trials (RCTs) comparing different dosing strategies and measuring clinically relevant outcomes, but we would also include RCTs evaluating the efficacy of intravenous theophyllines compared with placebo or other treatment, with subsequent analyses performed for each comparator drug, and observational studies.…”
Section: Methodsmentioning
confidence: 99%
“…The treatment of acute asthma in children should be guided by evidence of improvement of clinically relevant outcomes [ 15 , 16 ]. A recent systematic review found no evidence to support improved efficacy of aminophylline once the serum concentration increases above the lower threshold of 10mg/L, nor increased toxicity at levels above 20mg/l [ 17 ]. As the current therapeutic range is a poor guide to efficacy, an alternative dosing strategy may improve the optimum efficacy and safety profile of aminophylline.…”
Section: Introductionmentioning
confidence: 99%
“…Aminofilin dozu düzenlenmesinde yaş, ağırlık ve önceki serum konsantrasyonunun güvenilirliği bilinmemektedir ve önemli bireysel klirens farklılıkları vardır (55,56). Önerilen serum aminofilin konsantrasyonu 10-20 mg/L olsa da yeni yapılan sistematik bir review incelemede aminofilin serum konsantrasyonunun 10 mg/L' yi geçmesinin etkinlik artışında ya da 20 mg/l'yi geçtiğinde toksisite artışında bir katkı sağladığına dair kanıt olmadığı belirtilmiştir (57). Düzey takibi gerektiği de unutulmamalıdır.…”
Section: Aminofilinunclassified